Prove that (AUB)-(AB)=(A-B)u(B-A)
Answers
Answered by
1
Answer:
This question is based on set theory. The proof for the following is as follows.
Step-by-step explanation:
Let us consider that x ∈ (A-B) U (B-A)
Therfore we can write that
x ∈ (A-B) or x ∈ (B-A)
⇒ x ∈ A But x ∉ B or x ∈ B but x ∉ A,
⇒ x ∈ A or x ∈ B
⇒ x ∈ (A∪B)
⇒ x ∈ (A∪B) - (A∩B)
In this case, x represents the arbitrary element of the set (A-B) U (B-A).
So we can conclude that,
(A-B) U (B-A) = (A∪B) - (A∩B)
Hence, proved.
Similar questions